Common and distinctive adaptive traits expressed in Dickeya dianthicola and Dickeya solani pathogens when exploiting potato plant host. (27th January 2019) - Raoul des Essarts, Yannick; Pédron, Jacques; Blin, Pauline; Van Dijk, Erwin; Faure, Denis; Van Gijsegem, Frédérique
Summary: Blackleg and soft rot are devastating diseases on potato stem and tuber caused by Pectobacterium and Dickeya pectinolytic enterobacteria. In European potato cultures, D. dianthicola and D. solani species successively emerged in the past decades. Ecological traits associated to their settlement remain elusive, especially in the case of the recent invader D. solani . In this work, we combined genomic, metabolic and transcriptomic comparisons to unravel common and distinctive genetic and functional characteristics between two D. solani and D. dianthicola isolates. The two strains differ by more than a thousand genes that are often clustered in genomic regions (GRs). Several GRs code for transport and metabolism functions that correlate with some of the differences in metabolic abilities identified between the two Dickeya strains. About 800 D. dianthicola and 1100 D. solani genes where differentially expressed in macerated potato tubers as compared to when growing in rich medium. These include several genes located in GRs, pointing to a potential role in host interaction. In addition, some genes common to both species, including virulence genes, differed in their expression. This work highlighted distinctive traits when D. dianthicola and D. solani exploit the host as a resource.